Wojna na Lubelszczyźnie w latach 1914-1915 w świetle wspomnień - Korzeniowski, Mariusz (Przegląd Wschodnioeuropejski, 2019)
The present publication discusses the attitude of the residents of the Lublin area towards the outbreak, the course and outcome of the war, as well as its impact on the everyday life of civilian population in the years 1914–1915. The memoirs and personal accounts chosen to this end allow for the determination of the prevailing social attitudes, as they reflect the opinions of not just the well-educated and self-conscious strata, but also the “silent” part of the society, i.e. that which had been affected the most by the war, and where the majority of refugees originated from – both during the local resettlements in 1914, and the forced migration of the citizens of Congress Poland into Russia’s interior, caused by the soulless decisions of the Russian authorities in the following year.